VACCINE COVERAGE GAPS AND ERRORS - Sknar , Solomiia (Collection of scientific papers «ΛΌГOΣ», 2023)
Vaccine is a simple and at the same time effective way to protect an individual against harmful diseases before he or she contacts it. It makes his or her immune system stronger, using the body’s natural defenses to build specific resistance to specific infections. Because of some non- modifying factors, such as age or health conditions which cannot be treated, some people should not get certain vaccines or should wait before getting them. Unfortunately, some preventable events that may cause or lead to inappropriate use of vaccine or patient harm exist and they are known as vaccine administration errors. The types of immunization errors include overdose, the use of adult dose in children, the use of unapproved vaccines, inappropriate scheduling between doses, preparation errors (for example, omitting a diluent before immunization, administering the wrong vaccine), and the use of expired doses or vaccines.